Modeling of Reinforced Concrete Beams Exposed to Fire by Using a Spectral Approach - Rui Sun; Bo Xie; Ricardo Perera; Yongjun Pan (Advances in Materials Science and Engineering)
This paper presents a numerical procedure for predicting the mechanical behavior of reinforced concrete (RC) beams exposed to fire. Thermal behavior is captured using a two-dimensional finite element (FE) model in an environment of elevated temperatures, while a one-dimensional spectral numerical model is formulated to simulate the mechanical response of the beam under increasing loads. Both models are integrated. Previous thermal results obtained from the FE model are provided for the proposed numerical model to calculate the responses of the RC beam for different levels of fire exposure. Few elements are deployed in this study due to the simplicity and efficiency of the proposed numerical model. Consequently, the computational burden of the numerical simulation for predicting the structural performances of RC beams exposed to fire is released comparing with conventional FE model. The numerical results are consistent with the test data, which demonstrate the model’s capability of efficiently simulating the thermomechanical behaviors of RC beams due to its simplicity and accuracy.